Faktor Penentu Minat Menggunakan Financial Technology Syariah Pasca Covid-19 - Kurniawan, Arifa; Ningsih, Nur Wahyu; Pramasha, Raizky Rienaldy; Audia, Nanda (BISNIS, 2023)
The Covid-19 pandemic has shaped people's behavior patterns to utilize technology to facilitate activities. Technological innovations used in the financial sector with Islamic concepts are called sharia financial technology. This study aims to prove the theoretical concepts of planned behavior (attitudes, subjective norms, and perceptions of behavior control), the use of technology, Islamic financial literacy and digital literacy influence students' interest in using Islamic financial technology. This study uses a quantitative method with an explanatory research approach. The population in this study were FEBI UIN RIL students. The sampling method used accidental sampling with a total sample of 221 respondents. Data collection techniques using a questionnaire. The data analysis technique used the structural equation model-Partial Least Square (SEM-PLS) with the Warpls 7.0 tool. The results of the study prove that the variables attitude (X1), perceived behavioural control (X3), digital literacy (X5), and use of technology (X6) influence students' intentions to use Islamic financial technology. Meanwhile, the subjective norm variables (X2) and Islamic financial literacy (X4) have no effect on students' intentions to use Islamic financial technology.